Caffeine in Tris Egg Yolk Citrate Extender Improves the Antioxidant Potential of Cryopreserved Surti Buck Semen - Bhut, Darshita Vijaybhai; Khasatiya, Chandubhai Talshibhai; Singh, Virendra Kumar (The Indian Journal of Animal Reproduction, 2024)
The study was conducted to evaluate the antioxidant action of caffeine at various concentrations in TEYC extenders.  In the present study, a total 64 ejaculates (16/buck) were collected from all four Surti bucks (age>12 months) i.e. two  collections/week for 8 weeks. Ejaculates at each collection were pooled and divided into four groups viz. C1 (Control),  C2, C3 and C4 having caffeine concentrations @ 0, 1, 3 and 5mM in TEYC extender, respectively with 100x106 sperm/ • Oxidative stress marker for lipid peroxidation (Malondialdehyde, MDA) and antioxidant (Glutathione, GSH) were  determined at initial, pre-freeze and post-thaw; whereas, motility degeneration rate (MDR) of sperms was evaluated  at pre-freeze and post-thaw. A decrease in GSH and an increase in MDA levels with elapse of time were found to be  significant (p
Keywords: Antioxidant; Caffeine; Cryopreserved Semen; Glutathione; Malondialdehyde; Motility Degeneration Rate; Surti Buck